2019
DOI: 10.1016/j.celrep.2019.09.051
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN5 Enriched Microdomains Provide a Platform for Dendritic Spine Maturation through Neuroligin-1 Clustering

Abstract: Graphical AbstractHighlights d TSPAN5 is expressed in pyramidal neurons and localizes mainly to dendritic spines d TSPAN5 interacts with neuroligin-1 and promotes its clustering d TSPAN5-neuroligin-1 complex is fundamental for dendritic spine maturation AUTHOR CONTRIBUTIONS Conceptualization, E.M. and M.P.; Methodology, I.C. and M.S.; Investigation, E.M., A.L., L.M., I.C., A.S., J.Z., and E.H.; Writing -Original Draft, E.M. and M.P.; Writing -Review & Editing, E.M., A.L., M.P., V.B., D.C., G.S., and O.T.; Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 95 publications
0
27
2
Order By: Relevance
“…Recent work from Moretto et al (2019) has demonstrated the significance of TSPAN5 in spine maturation. TSPAN5 is present during nearly every stage of spine maturation, beginning with filopodia, but seems to function primarily in the conversion of immature spines to mushroom spines.…”
Section: Tetraspanin 5 (Tspan5)mentioning
confidence: 99%
“…Recent work from Moretto et al (2019) has demonstrated the significance of TSPAN5 in spine maturation. TSPAN5 is present during nearly every stage of spine maturation, beginning with filopodia, but seems to function primarily in the conversion of immature spines to mushroom spines.…”
Section: Tetraspanin 5 (Tspan5)mentioning
confidence: 99%
“…Tetraspanin nanodomains are predominantly composed of homotypic tetraspanin interactions, with heterotypic tetraspanintetraspanin interactions only occurring at the borders of nanodomains, as shown by superresolution microscopy [31]. Interactions with binding partners can occur both at the border of tetraspanin nanodomains [31] and within nanodomains [28,33] (Figure 2C).…”
Section: Tetraspanin Proteins Form Organizing Nanodomainsmentioning
confidence: 95%
“…Later, fluorescence super-resolution microscopy revealed that tetraspanin clusters have a diameter of~100 nm [29,32]; as such, we put forward the name 'tetraspanin nanodomains.' Partner proteins can be localized inside these domains and/or at the edge [31,33].…”
Section: Box 2 a Short History Of Tetraspaninsmentioning
confidence: 99%
“…The cholesterol-binding protein TSPAN5, which belongs to the tetraspanin superfamily, is localized postsynaptically in pyramidal excitatory neurons, and is the master controller of spine maturation. Control is exerted by promoting the clustering of the postsynaptic molecule neuroligin-1 at the spine surface [ 197 ], which in turn recognizes and binds to presynaptic neurexins. TSPAN5 knockout mice have an extremely low number of spines, reinforcing the view that this tetraspanin plays a key role in excitatory synapse maturation.…”
Section: Nanodomain Cluster Organization Emerges As a Common Organizing Principle At Cns Synapsesmentioning
confidence: 99%